The Effect Of Using Typical Breathing Mechanism On Developing In Rowing Performance Recovery In Young League Rowers - Abedullateef, Ayad (Journal of Physical Education, 2017)
Every sport requires balance between physical fitness components like strength, speed and stamina, recovery, and oxygen uptake. The importance of the research lies in mastering typical breathing mechanism for quick recovery after rowing. The problem of the research lies in early signs of fatigue in young rowers. The aim of the research was to identify the effect of typical breathing mechanism on the developing rowing performance in young rowers. The researcher hypothesized statistical differences in breathing mechanism effect on rowing performance. The researcher used the experimental method. The subjects were (6) rowers. The data was collected and treated using proper statistical operations to conclude that typical breathing mechanism reduced physical effort and recovery time. Finally the researcher recommended making similar researches on other age groups and for longer distances